The student's Behavior Intention using Virtual Reality in Learning Environments - AlFarsi G.; Yusof A.B.M.; Rusli M.E.B.; Tawafak R.M.; Malik S.I.; Mathew R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Augmented reality; Computer aided instruction; E-learning; Engineering education; Learning systems; Students; (VRT) virtual reality technology; Behaviour intentions; Learner information; Learning domain; Learning environments; Life experiences; Students' behaviors; Technology; Technology centers; Virtual reality technology; Virtual reality